Töre bitiki metninden hareketle Gregoryan Muhiti Kıpçak Türkçesi terimi - ATALAN, SONER (My University, 2023)
Töre Bitiki, Gregoryan Kıpçakların hayatlarını düzenleyen, toplumsal ilişkilerini belirleyen bir hukuk metnidir. Mihitar Goş tarafından 12. yüzyılda Hay diliyle yazılan Dadastan Girk (Yargı Kitabı) 1518-1519 yılları arasında Hay dilinden Latinceye, 1523 yılında Kral I. Zigmont himayesinde Latinceden Lehçeye ve aynı tarihte Lehçeden Gregoryan Muhiti Kıpçak Türkçesine tercüme edilmiştir. Bu tercüme sırasında, Dadastan Girk’in giriş bölümü ve 98 maddesi Hay dilinden Kıpçak Türkçesine doğrudan tercüme edilmiş ve bu bölümlere ek olarak 24 madde Gregoryan Kıpçaklar tarafından Kıpçak Türkçesi ile eklenmiştir. Bu 24 ek madde dışında, Yargılama Usulü Yasaları bölümü tamamıyla Gregoryan Kıpçaklar tarafından yazılmıştır. Bu sayede Töre Bitiki metni sadece tercüme bir metin değil aynı zamanda Gregoryan Kıpçaklar tarafından yeniden oluşturulmuş bir metin olma özelliği kazanmıştır. Bu çalışmada önce, Gregoryan Kıpçaklar, Kıpçakların Gürcü ve Haylarla ilişkileri, Töre Bitiki’nin oluşum süreci, nüshaları ve içeriği hakkında bilgiler verilmiştir. Sonrasında, metninde eserin dili hakkında yazılan açıklamalar ve eserdeki millet ve dil ayrımları incelenmiştir. Bu metinde yer alan dil ve millet bilgileri aynı dille yazılan diğer eserlerdeki bilgiler ile birlikte değerlendirilmiştir. Bu bilgiler ışığında bu eserlerin yazıldığı dilin Gregoryan Muhiti Kıpçak Türkçesi terimi ile isimlendirilmesinin gerekçeleri sunulmuştur.

Tore Bitiki is a law text that is used to regulate the lives of the Gregorian Kipchaks and to determine their social relationships. The Dadastan Girk (Book of Judgments), written in the Hay language by Mihitar Goş in the 12th century, was translated from the Hay language into Latin between 1518-1519. It was translated from Latin into Polish under the auspices of King Zigmont I later in 1523, and from Polish into Gregorian Zone Kipchak Turkish at roughly the same time. During these translations, the introductory chapter and 98 articles of Dadastan Girk were translated literally from Hay into Kipchak Turkish, and an additional 24 articles were added by the Gregorian Kipchaks in Kipchak Turkish. Apart from these 24 additional articles, the Code of Judicial Conduct was written entirely by Gregorian Kipchaks. In this way, the text of Tore Bitiki has gained the characteristic of being not only a translated text but also a text re-created by the Gregorian Kipchaks. reconstructed by the Gregorian Kipchaks. In this study, information about the Gregorian Kipchaks, the relations of the Kipchaks with the Georgians and Hays, the formation process, copies and content of the Tore Bitiki are presented Following this, the remarks in the text about the language of the work and the distinctions between nation and language were analysed. The language and nationality references in this text has been evaluated with the references in other works written in the same language. Based on this information, the reasons why the language of these texts is called Gregorian Zone Kipchak Turkish are explained.
The Term of Gregorian Zone Kipchak Turkish Based on the Text of Tore Bitiki
Keywords: Töre Bitiki; Yasa Kitabı; Gregoryan Muhiti Kıpçak Türkçesi; Kıpçaklar; Gregoryan Kıpçaklar; Doğu Avrupa; Tore Bitiki; Book of Laws; Gregorian Zone Kipchak Turkish; Kipchaks; Gregorian Kipchaks; Eastern Europe